Lyle Burns interviewed by Kay Lawrence in the Parliament House embroiderers oral history project - Burns, Lyle, 1946-; Lawrence, Kay, 1947- (2012)
Lyle Burns speaks about her childhood; her parents and their background and their occupation; her siblings; her schooling and education; New Zealand; her relationships; health; her career in accountancy; tertiary study; her interest in embroidery; the Queensland Embroiderers Guild; her daughters; Aboriginal people; lacemaking tours overseas; Tindale Map; community involvement; OIDFA (International Bobbin and Needle Lace Organisation); the people and factors that have shaped her life and her values.
Recorded on 16, 18 November 2012 in Brisbane, Qld.
Digital master available
Summary not yet available.
Keywords: Burns, Lyle, -- 1946- -- Interviews; Bookkeepers -- Queensland -- Interviews; Accountants